PENERAPAN METODE MENDONGENG DALAM PEMBELAJARAN ELECTONE DASAR BAGI ANAK USIA DINI DI YAMAHA MUSIC SCHOOL KUDUS - Pratidina, Nirmala Nandya; widjajantie, kusrina (Jurnal Seni Musik, 2017)
Storytelling method is a way to achieve learning purposes through storytelling so that learners are more enthusiastic in following a lesson. This study aims to know, describe, and conclude how the use of storytelling method in basic electone classes for toddlers in Kudus Yamaha Music School. This study uses qualitative methods with data collection through nontest techniques such as observation, interviews, and documentation. The results of this study are as follows know the use of storytelling method in basic electone classes and how the attitude of students in learning activities. As a result, the selection of music terms likened to fairy tales is also deemed appropriate and relevant. The simulation of music terms in fairy tales also matches with the age and capability of learners. In addition, students aged between 4 and 5 years old become more enthusiastic in listening to teachers in delivering teaching materials when taught by the storytelling method. Keywords: storytelling, early childhood, electone classes